Covalent organic framework pervaporation hybrid membrane for regulating interlayer structure based on combination sequence, and preparation and application of covalent organic framework pervaporation hybrid membrane

Through the preparation method of covalent organic frame permeation vaporization hybrid film that combines the covalent organic frame structure, the channel size and assembly problems of COF membrane in butanol dehydration application are solved, and efficient water/butanol separation is achieved and the penetration is improved. Flux and separation factors and maintain stable performance under high temperature and high concentration environments.

CN119139928AActive Publication Date: 2024-12-17NANJING TECH UNIV

Patent Information

Application Number
CN202411333379.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The application of existing COF membranes in butanol dehydration is limited by inaccurate channel size and nanosheet assembly problems, resulting in poor performance and limited application in small molecule separation.

Method used

The preparation method of permeable vaporization hybrid film of covalent organic frames that regulate interlayer structures in combination and sequence is used to form a highly hydrophilic surface and hydrophobic part through the reaction of aldehyde and amino organic monomers, interaction between polyelectrolytes and metal ions, and to build a precise Water molecule transport channel to achieve uniform film formation and efficient separation of COF nanosheets.

Benefits of technology

The permeable vaporized membrane with high throughput and high separation factors can effectively intercept butanol molecules, increase the permeability flux, significantly improve the separation factor, and maintain stable performance in high temperature and high concentration environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139928A_ABST
    Figure CN119139928A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of pervaporation membrane preparation and application, and relates to a covalent organic framework pervaporation hybrid membrane with a combination sequence regulation interlayer structure, in particular to preparation of the pervaporation membrane and application of the pervaporation membrane in water / butanol separation. Adding the aldehyde monomer solution into the amino monomer solution, and standing for reaction; taking a water phase, and carrying out dialysis treatment; diluting the covalent organic framework nanosheet dispersion liquid to obtain dispersion liquid A; adjusting the pH of a polyelectrolyte aqueous solution to obtain a solution B; adjusting the pH value of the metal ion dispersion liquid to obtain a solution C; uniformly mixing the dispersion liquid A and the solution C at normal temperature, adding the solution B, and heating for reaction to obtain a membrane casting liquid; and carrying out suction filtration on the membrane casting solution to a base membrane, and carrying out vacuum drying to obtain the pervaporation membrane. At 70 DEG C, the separation flux of a 10wt% / 90wt% water / butanol mixture is 7.52 g / (m < 2 > h), and the separation factor reaches 13709.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pervaporation membrane preparation and application, and relates to a covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure, and specifically relates to the preparation of the pervaporation membrane and its application in water / butanol separation. Background Art

[0002] Butanol is a key chemical in the industrial field. It is both a solvent and a renewable biofuel. The dehydration of butanol is extremely important in the chemical industry. Compared with the traditional distillation process, membrane pervaporation (PV) technology has attracted widespread attention due to its higher efficiency, pollution-free and low energy consumption. The selection and preparation of high-performance membrane materials are the key points in the application of pervaporation technology. In recent years, ultra-thin separation membranes prepared by two-dimensional nanosheets represented by graphene oxide (GO) have been widely studied, and their separation performance has broken through the performance bottleneck of traditional polymer membrane materials. However, graphene oxide nanosheets are approximately non-porous structures, and the mass transfer channels in the membrane are tortuous, resulting in a relatively limited increase in permeation flux. The new two-dimensional (2D) COF nanosheets have high-density regular pores, high functional control freedom and excellent structural stability. After being assembled into membranes, it is expected to achieve high flux and has become an important research topic in the field of water treatment. However, there are great challenges in applying COF membranes to the pervaporation process: on the one hand, the large channel size of COF makes it difficult to achieve precise size screening, limiting its application in small molecule separation; on the other hand, COF nanosheets are difficult to assemble directly into membranes. Specifically, ionic COF nanosheets are difficult to assemble regularly due to the strong repulsion between each other, while the π-π stacking effect between non-ionic COF nanosheets will cause them to agglomerate. Due to the above two reasons, there are currently very few studies on the application of COF membranes in the butanol dehydration process, and the performance is not ideal. Therefore, it is necessary to develop a new COF membrane preparation method to obtain a high-throughput, high-separation factor COF pervaporation membrane, so as to achieve the preparation of high-purity butanol. Summary of the invention

[0003] In view of the challenges faced by the above-mentioned COF membrane in the pervaporation process for preparing high-purity butanol, the present invention proposes a novel covalent organic framework pervaporation hybrid membrane with a combined sequentially regulated interlayer structure and its application in water / butanol separation.

[0004] In order to achieve the above object, the present invention is implemented by adopting the following technical solutions: A method for preparing a covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure, wherein the pervaporation membrane comprises a substrate and a functional layer, and the steps are as follows: (1) dissolving an aldehyde organic monomer in an organic solvent and mixing them uniformly to obtain an aldehyde monomer solution; dissolving an amino organic monomer in deionized water and mixing them uniformly to obtain an amino monomer solution; adding the aldehyde monomer solution to the amino monomer solution and allowing the solution to react; after the reaction is completed, taking the aqueous phase and dialyzing it to obtain a covalent organic framework nanosheet dispersion.

[0005] (2) The covalent organic framework nanosheet dispersion is diluted and the pH is adjusted to neutral to obtain dispersion A; a polyelectrolyte aqueous solution is prepared and the pH is adjusted to neutral to obtain solution B; a metal ion dispersion is prepared and the pH is adjusted to neutral to obtain solution C.

[0006] (3) Dispersion A and solution C are mixed at room temperature and stirred evenly, then solution B is added, stirred and heated to react, and after the reaction is completed, it is naturally cooled to room temperature to obtain a casting solution.

[0007] (4) The casting liquid is filtered onto the base membrane and vacuum dried to obtain a pervaporation membrane.

[0008] Preferably, in step (1), the concentration of the aldehyde monomer solution is 1-10 mmol / L; the amino monomer solution is a mixture of an amino organic monomer and an auxiliary agent, the molar concentrations of the amino organic monomer and the auxiliary agent are both 1-10 mmol / L, and the molar ratio of the aldehyde monomer to the amino monomer is 1:(1-3); the static reaction time is 4-6 days, and the dialysis treatment time is 2-4 days; the auxiliary agent is sodium carbonate or p-toluenesulfonic acid.

[0009] Preferably, the metal ion in step (2) is any one of sodium ion, potassium ion, magnesium ion, calcium ion, zinc ion, copper ion, aluminum ion and iron ion; the covalent organic framework nanosheet is any one of TpPa-SO3H or TpEB, and the covalent organic framework nanosheet is prepared by interfacial polymerization; the polyelectrolyte is any one of polyethyleneimine, sodium alginate, polyacrylic acid and polyethyleneamine.

[0010] Preferably, in step (2), the concentration of the covalent organic framework dispersion in dispersion A is 0.01-0.03 mg / ml, the concentration of the polyelectrolyte solution in solution B is 0.01-0.03 mg / ml, the concentration of the metal ions in solution C is 3-4 mmol / L, and the volume ratio of dispersion A: solution B: solution C is (1-2): (2-3): (1-2).

[0011] Preferably, in step (3), the dispersion A and solution C are mixed and stirred at room temperature for 8-15 min, and after solution B is added, the temperature of the reaction is raised to 75-85° C., and the reaction time is 0.9-1.2 h.

[0012] The present invention proposes the use of a covalent organic framework pervaporation hybrid membrane with a combined sequentially regulated interlayer structure obtained by the preparation method in water / butanol separation.

[0013] In the preparation method provided by the present invention, on the one hand, the polyelectrolyte induces the covalent organic framework nanosheet to form a uniform film through electrostatic action; on the other hand, the polymer chain segments fully move and gather around the covalent organic framework, which improves the hydrophilicity and reduces the channel size; finally, the interaction between the metal ions, the covalent organic framework and the polyelectrolyte is used to control the combination order of the three to form the optimal microscopic channel structure, and construct a precise and efficient water molecule transmission channel. The specific process is: the polyelectrolyte, the metal ions and the covalent organic framework are all made into a dispersion / solution, after adjusting the pH, the polyelectrolyte solution and the covalent organic framework dispersion are mixed at room temperature, and then the metal ion solution is added to heat and stir to react to obtain a mixed solution. The obtained mixed solution is co-assembled on the surface of the base membrane by a vacuum-assisted filtration method to prepare a covalent organic framework pervaporation hybrid membrane. Among them, the amino groups, metal ions and sulfonic acid groups on the polyelectrolyte-rich covalent organic framework are all highly hydrophilic, and the hydrophilic segments will also cover the hydrophobic parts on the covalent organic framework, forming a highly hydrophilic surface of the hybrid membrane material, cooperating with the hydrophobic covalent organic framework in the middle, and finally realizing the selective adsorption and rapid transmission of water molecules. The above effects can achieve a simultaneous increase in the flux and separation factor of the pervaporation membrane.

[0014] Compared with the prior art, the advantages and positive effects of the present invention are: 1. The preparation method of the present invention is simple and controllable. The prepared covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure can be used at 70 o C, the permeation flux of the pervaporation separation of 10wt% / 90wt% water / butanol mixture is 7.52 kg / (m 2 h), the separation factor for butanol reaches 13709, which can effectively retain butanol molecules.

[0015] 2. The pervaporation membrane prepared by the present invention has excellent stability and can adapt to high temperature and high concentration working environment. After continuous monitoring for 360 hours, the pervaporation membrane performance remains stable. It can be used for pervaporation water / butanol separation and has broad application prospects in solvent separation and purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XPS characterization of the pervaporation membrane obtained in Example 1 shows that Zn 2+ Fine spectrum.

[0017] Figure 2 1 is a performance diagram of the pervaporation membrane obtained in Example 1 at different feed liquid temperatures (feed liquid concentration 10 wt % water / butanol).

[0018] Figure 3 This is a performance diagram of the pervaporation membrane obtained in Example 1 at different feed liquid water concentrations (feed liquid temperature 70°C). DETAILED DESCRIPTION

[0019] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.

[0021] Example 1 This embodiment provides a method for preparing a covalent organic framework pervaporation hybrid membrane with combined sequential regulation of interlayer structure.

[0022] 0.1mmol of trialdehyde phloroglucinol was dissolved in 20ml of n-octanoic acid and stirred until uniformly mixed to obtain an aldehyde monomer solution. 0.15mmol of 2,5-diaminobenzenesulfonic acid and 0.15mmol of sodium carbonate were dissolved in 30ml of water and stirred to obtain an amino monomer solution. Then the aldehyde monomer solution was poured into the amino monomer solution, sealed and allowed to react for 5 days at room temperature. After the reaction was completed, the organic layer was discarded, the aqueous phase mixture was taken, and dialyzed with a dialysis bag (MW1000, Jelupu) for 3 days to obtain a TpPa-SO3H nanosheet dispersion.

[0023] The concentration of the obtained TpPa-SO3H nanosheet dispersion was determined by sampling and drying, and then the volume of the TpPa-SO3H nanosheet dispersion required was calculated according to the final concentration of 0.02 mg / ml, and deionized water was added to dilute it to 5 ml. 10 ml of 0.02 mg / mL polyvinylamine (PEAm, Mw=70k) aqueous solution was prepared, and then 5 ml of 3.1 mmol / L zinc nitrate aqueous solution was prepared. The above three solutions or dispersions were adjusted to pH 7 by sodium hydroxide solution or hydrochloric acid solution (the concentration of sodium hydroxide solution or hydrochloric acid solution was 2 mol / L) for standby use. After the pH adjustment was completed, the TpPa-SO3H nanosheet dispersion was first blended with the zinc nitrate aqueous solution and stirred at room temperature for 10 min; then the polyvinylamine aqueous solution was added and stirred evenly, and then added to an 80°C water bath and continued to stir for 1 h, with a stirring rate of 200-500 rpm. After the reaction was completed, it was naturally cooled to room temperature to obtain a mixed solution.

[0024] The mixed solution obtained in the above steps was filtered onto a porous polyacrylonitrile-based membrane (circular flat ultrafiltration membrane, 4 cm in diameter, MWCO: 100 kDa, Shandong Lanjing Membrane Technology Engineering Co., Ltd., China) to prepare a functional layer. After the membrane surface was completely dried, it was vacuum dried at room temperature for 2 h to obtain a covalent organic framework pervaporation hybrid membrane with a combined sequentially regulated interlayer structure.

[0025] Since the TpPa-SO3H nanosheet dispersion was first mixed with the zinc nitrate aqueous solution, the covalent organic framework first 2+ The pervaporation membrane prepared in this example was characterized by XPS. The results are as follows: Figure 1 ,according to Figure 1 Zn in XPS 2+ The fine peak spectrum shows that the Zn←O peak area in the covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure prepared in this embodiment is 58.42%, which is 34.59% of the Zn←O peak area of ​​the membrane in Comparative Example 1, further proving that in this embodiment, the covalent organic framework first reacts with Zn 2+ The cross-linking effect of the formation of the polyelectrolyte makes it form a close arrangement before blending with the polyelectrolyte, which ultimately leads to a compact and rich interlayer of polyelectrolyte and Zn 2+ The membrane has a channel structure of 70 o C, the permeation flux of the pervaporation separation of 10wt% / 90wt% water / butanol mixture is 7.52kg / (m 2 h), the water / butanol separation factor is 13709. Under this condition, the pervaporation membrane performance remained stable after 360 hours of continuous monitoring.

[0026] Example 2 The present embodiment is consistent with the embodiment 1 unless otherwise specified.

[0027] Dissolve 0.1mmol of trialdehyde phloroglucinol in 100ml of dichloromethane, stir until mixed evenly, and obtain an aldehyde monomer solution. Dissolve 0.3mmol of ethidium bromide and 0.3mmol of p-toluenesulfonic acid in 100ml of water, stir until mixed evenly, and obtain an amino monomer solution. Then pour the aldehyde monomer solution into the amino monomer solution, seal and stand for reaction at room temperature for 5 days, discard the organic layer after the reaction, take the aqueous phase mixture, and dialyze it with a dialysis bag for 3 days to obtain a TpEB nanosheet dispersion.

[0028] The concentration of the obtained TpEB nanosheet dispersion was determined by sampling and drying, and then the volume of TpEB nanosheet dispersion required was calculated according to the concentration of 0.023 mg / ml, and the sample was diluted to 6 ml by adding deionized water. 13 ml of sodium alginate aqueous solution with a concentration of 0.027 mg / mL was prepared, and then 7 ml of sodium nitrate aqueous solution with a concentration of 3.3 mmol / L was prepared. The pH of the above three solutions or dispersions was adjusted to 7 by sodium hydroxide solution or hydrochloric acid solution for standby use. After the pH adjustment was completed, the TpEB nanosheet dispersion was first blended with the zinc nitrate aqueous solution and stirred at room temperature for 13 min; then the sodium alginate (SA) aqueous solution was added and stirred evenly, and then added to an 80°C water bath and continued to stir for 1 h, with a stirring rate of 200-500 rpm. After the reaction was completed, it was naturally cooled to room temperature to obtain a mixed solution.

[0029] The mixed solution obtained in the above steps was filtered onto a porous polyacrylonitrile-based membrane. After the membrane surface was completely dried, it was vacuum dried at room temperature for 2 hours to obtain a covalent organic framework pervaporation hybrid membrane with a combined sequentially regulated interlayer structure.

[0030] The pervaporation membrane prepared in this example was characterized by XPS. The Na←O peak area in the covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure prepared in this example was 60.01%, which was much larger than the Zn←O peak area of ​​34.59% in the membrane of Comparative Example 1. This also proved that the interaction between the nanosheets was strong, resulting in a compact and rich interlayer structure of polyelectrolytes and Na + The permeation flux of the membrane for the pervaporation separation of a 10wt% / 90wt% water / butanol mixture at 70°C is 11.03kg / (m 2 h), the water / butanol separation factor is 25563.

[0031] Example 3 The present embodiment is consistent with the embodiment 1 unless otherwise specified.

[0032] Dissolve 0.2mmol of trialdehyde phloroglucinol in 20ml of n-octanoic acid, stir until mixed evenly, and obtain an aldehyde monomer solution. Dissolve 0.3mmol of 2,5-diaminobenzenesulfonic acid and 0.3mmol of sodium carbonate in 30ml of water, stir until mixed evenly, and obtain an amino monomer solution. Then pour the aldehyde monomer solution into the amino monomer solution, seal and stand for reaction at room temperature for 4 days, discard the organic layer after the reaction, take the aqueous phase mixture, and dialyze it with a dialysis bag for 4 days to obtain a TpPa-SO3H nanosheet dispersion.

[0033] The concentration of the obtained TpPa-SO3H nanosheet dispersion was determined by sampling and drying, and then the volume of the TpPa-SO3H nanosheet dispersion required was calculated according to the concentration of 0.028 mg / ml, and the sample was diluted to 9 ml by adding deionized water. 15 ml of 0.025 mg / mL polyvinylamine (PEAm, Mw=70k) aqueous solution was prepared, and then 7 ml of 3.6 mmol / L sodium nitrate aqueous solution was prepared. The pH of the above three solutions or dispersions was adjusted to 7 by sodium hydroxide solution or hydrochloric acid solution for standby use. After the pH adjustment was completed, the TpPa-SO3H nanosheet dispersion was first blended with the sodium nitrate aqueous solution and stirred at room temperature for 15 min; then the polyethyleneimine (PEI, Mw=10k) aqueous solution was added and stirred evenly, and then added to an 83°C water bath and continued to stir for 1 h, with a stirring rate of 200-500 rpm. After the reaction was completed, it was naturally cooled to room temperature to obtain a mixed solution.

[0034] The mixed solution obtained in the above steps was filtered onto a porous polyacrylonitrile-based membrane. After the membrane surface was completely dried, it was vacuum dried at room temperature for 2 hours to obtain a covalent organic framework pervaporation hybrid membrane with a combined sequentially regulated interlayer structure.

[0035] The pervaporation membrane prepared in this example was characterized by XPS. The Na←O peak area in the covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure prepared in this example was 57.35%, which was larger than the Zn←O peak area of ​​34.59% in the membrane of Comparative Example 1. + Electrostatic interactions and cation-π interactions are formed. Before the addition of polyelectrolytes, the interaction between nanosheets is strong, resulting in compactness and rich interlayers of polyelectrolytes and Na + The permeation flux of the membrane for the pervaporation separation of a 10wt% / 90wt% water / butanol mixture at 70°C is 7.78kg / (m 2 h), the water / butanol separation factor is 12033.

[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that when preparing the casting solution, after the pH of each solution or dispersion is adjusted to neutral, the polyvinylamine aqueous dispersion solution and the zinc nitrate aqueous solution are first mixed, stirred at room temperature for 10 min, and then stirred evenly with the diluted TpPa-SO3H nanosheet dispersion, and stirred and reacted at 80°C for 1 h. The other conditions and preparation process are consistent with Example 1.

[0037] The pervaporation membrane prepared in this comparative example was characterized by XPS. The results showed that the peak area of ​​Zn←O was 34.59%, and the peak area of ​​Zn←N was 65.41%. Compared with Example 123, the peak area of ​​Zn←O accounted for a smaller proportion, indicating that the polyelectrolyte first reacted with Zn 2+ The coordination effect is formed, which weakens the interaction between it and the covalent organic framework, resulting in a loose structure but rich in polyelectrolytes and Zn 2+ The channel structure of the membrane is 70 o C, the permeation flux of the pervaporation separation of 10wt% / 90wt% water / butanol mixture is 8.06kg / (m 2 h), the water / butanol separation factor is 7952.

[0038] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing the casting solution, after the pH of each solution or dispersion is adjusted to neutral, the polyvinylamine aqueous dispersion solution is first blended with the diluted TpPa-SO3H nanosheet dispersion solution, stirred at room temperature for 10 minutes, and then stirred evenly with the zinc nitrate aqueous solution, and stirred and reacted at 80°C for 1 hour. The other conditions and preparation process are consistent with Example 1.

[0039] The pervaporation membrane prepared in this comparative example was characterized by XPS. The results showed that the peak area of ​​Zn←O was 41.98%, and the peak area of ​​Zn←N was 58.02%. The polyelectrolyte first interacted with the covalent organic framework. 2+ The larger hydration radius makes it difficult for it to enter the interior of the nanocomposite material, and it only interacts with the organic framework and the polyelectrolyte at the gap. Therefore, compared with Example 123 and Comparative Example 1, its Zn←O peak area is between the two, and finally a more compact channel structure with only polyelectrolyte between the layers is formed. o C, the permeation flux of the pervaporation separation of 10wt% / 90wt% water / butanol mixture is 6.08kg / (m 2 h), the water / butanol separation factor is 5407.

[0040] It can be seen from the results of Comparative Examples 1 and 2 that the mixing of the polyelectrolyte solution, the metal ion solution and the covalent organic framework dispersion in different combinations has a significant effect on the microscopic interlayer structure and separation performance of the pervaporation membrane.

[0041] Comparative Example 3 The difference between this comparative example and Example 1 is that no metal ion solution is added to the casting solution, and only the polyvinylamine aqueous dispersion and the diluted TpPa-SO3H nanosheet dispersion are stirred and reacted at 80°C for 1 h. The other conditions and preparation process are consistent with Example 1.

[0042] XPS characterization revealed that no metal ions were detected in the polyelectrolyte-covalent organic framework membrane without metal ions in the comparative example. oC The permeation flux of the pervaporation separation of 10wt% / 90wt% water / butanol mixture is 4.12kg / (m 2 h), the water / butanol separation factor is 2573.

[0043] 1. Investigation of the stability of pervaporation membranes relative to temperature The pervaporation membrane prepared in Example 1 was used to separate 10 wt% water / butanol materials, and the effect of different temperatures on the membrane separation performance was investigated. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the membrane flux and separation factor both show an upward trend with increasing temperature, which is very difficult to achieve in separation membranes.

[0044] 2. Study on the stability of pervaporation membrane relative to material concentration The pervaporation membrane prepared in Example 1 was used to separate water / butanol materials with different concentration ratios at 70°C to investigate the effect of material concentration on the separation performance of the pervaporation membrane. The results are as follows: Figure 3 As shown in the figure, within the test range, the flux and separation factor both show an upward trend, indicating that under the environment of ultra-high water concentration, the pervaporation membrane prepared in Example 1 can still maintain high flux and high separation accuracy.

[0045] The present invention uses a covalent organic framework as a material, introduces a polyelectrolyte to reduce the COF pore size, uses covalent and electrostatic effects to induce the regular arrangement of COF nanosheets, and uses the strong hydrophilicity / water absorption ability of the polyelectrolyte to construct a rapid water molecule transmission channel; introduces metal ions, uses electrostatic interaction and cation-π interaction to regulate the water molecule transmission channel; polyelectrolytes cooperate with metal ions to achieve simultaneous improvement of the flux and separation factor of the covalent organic framework pervaporation membrane. The covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure prepared by the present invention can achieve high water flux and high-precision separation of water / butanol molecules, and its preparation method is convenient and simple.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure, wherein the pervaporation membrane comprises a substrate and a functional layer, characterized in that: The steps are as follows: (1) dissolving an aldehyde organic monomer in an organic solvent and mixing them uniformly to obtain an aldehyde monomer solution; dissolving an amino organic monomer in deionized water and mixing them uniformly to obtain an amino monomer solution; The aldehyde monomer solution is added to the amino monomer solution and allowed to stand for reaction; after the reaction is completed, the aqueous phase is taken and dialyzed to obtain a covalent organic framework nanosheet dispersion; (2) diluting the covalent organic framework nanosheet dispersion and adjusting the pH to neutral to obtain dispersion A; preparing a polyelectrolyte aqueous solution and adjusting the pH to neutral to obtain solution B; Prepare a metal ion dispersion and adjust the pH to neutral to obtain solution C; (3) Dispersion A and solution C are mixed at room temperature and stirred evenly, then solution B is added, stirred and heated to react, and after the reaction is completed, the mixture is naturally cooled to room temperature to obtain a casting solution; (4) The casting liquid is filtered onto the base membrane and vacuum dried to obtain a pervaporation membrane.

2. The method for preparing a covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure according to claim 1, characterized in that: The concentration of the aldehyde monomer solution in step (1) is 1-10 mmol / L; the amino monomer solution is a mixed solution of an amino organic monomer and an auxiliary agent, the molar concentrations of the amino organic monomer and the auxiliary agent are both 1-10 mmol / L, and the molar ratio of the aldehyde monomer to the amino monomer is 1:(1-3); the static reaction time is 4-6 days, and the dialysis treatment time is 2-4 days; the auxiliary agent is sodium carbonate or p-toluenesulfonic acid.

3. The method for preparing a covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure according to claim 1, characterized in that: The metal ion described in step (2) is any one of sodium ion, potassium ion, magnesium ion, calcium ion, zinc ion, copper ion, aluminum ion, and iron ion; the covalent organic framework nanosheet is any one of TpPa-SO3H or TpEB; and the polyelectrolyte is any one of polyethyleneimine, sodium alginate, polyacrylic acid, or polyethyleneamine.

4. The method for preparing a covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure according to claim 1, characterized in that: In step (2), the concentration of the covalent organic framework dispersion in dispersion A is 0.01-0.03 mg / ml, the concentration of the polyelectrolyte solution in solution B is 0.01-0.03 mg / ml, the concentration of the metal ion in solution C is 3-4 mmol / L, and the volume ratio of dispersion A: solution B: solution C is (1-2): (2-3): (1-2).

5. The method for preparing a covalent organic framework pervaporation hybrid membrane with sequentially controlled interlayer structure according to claim 1, characterized in that: In step (3), the dispersion A and solution C are mixed and stirred at room temperature for 8-15 minutes, and after solution B is added, the temperature of the reaction is raised to 75-85°C, and the reaction time is 0.9-1.2 hours.

6. Use of the covalent organic framework pervaporation hybrid membrane with combined sequentially regulated interlayer structure obtained by the preparation method according to any one of claims 1 to 5 in water / butanol separation.

Citation Information

Patent Citations

  • Method for preparing two-dimensional covalent organic framework ultrathin nanosheet material composite film and application of two-dimensional covalent organic framework ultrathin nanosheet material composite film

    CN112973468A

  • Covalent organic framework doped polyamide reverse osmosis membrane and preparation method thereof

    CN114618331A

  • Polyelectrolyte / covalent organic framework nanosheet hybrid membrane as well as preparation method and application thereof

    CN116236918A

  • Conductive polymer-containing liquid and production method thereof, and conductive film and production method thereof

    JP2020100709A

Cited By

  • Ionic covalent organic framework membrane as well as preparation method and application thereof

    CN119565394A

  • An ionic covalent organic framework membrane and a preparation method and application thereof

    CN119565394B

  • Covalent organic framework material solid phase microextraction fiber and application thereof in alkaloid metabolism and neurotransmitter analysis

    CN119684549A

  • Preparation method for in-situ polymerization of sodium polyacrylate hydrogel containing covalent organic framework material

    CN119978434A

  • A method for preparing sodium polyacrylate hydrogel containing covalent organic framework material by in situ polymerization

    CN119978434B